2012
DOI: 10.1002/hep.25849
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-induced up-regulation of microRNA-155 promotes hepatocarcinogenesis by activating Wnt signaling

Abstract: Hepatitis C virus (HCV) infection usually induces chronic hepatic inflammation, which favors the initiation and progression of hepatocellular carcinoma (HCC). Moreover, microRNA-155 (miR-155) plays an important role in regulating both inflammation and tumorigenesis. However, little is known about whether and how miR-155 provides the link between inflammation and cancer. In this study we found that miR-155 levels were markedly increased in patients infected with HCV. MiR-155 transcription was regulated by nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
218
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(231 citation statements)
references
References 30 publications
9
218
1
1
Order By: Relevance
“…Subsequent experiments demonstrated that miR-155-induced suppression of HBP1 accounted for its effects on activation of the Wnt/β-catenin signaling pathway. Previous studies have revealed that overexpression of miR-155 promotes activation of the Wnt/β-catenin signaling pathway (16,17). However, these findings were attributed to miR-155-induced activation of Wnt/β-catenin signaling to suppression of adenomatous polyposis coli, a Wnt/β-catenin inhibitor.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequent experiments demonstrated that miR-155-induced suppression of HBP1 accounted for its effects on activation of the Wnt/β-catenin signaling pathway. Previous studies have revealed that overexpression of miR-155 promotes activation of the Wnt/β-catenin signaling pathway (16,17). However, these findings were attributed to miR-155-induced activation of Wnt/β-catenin signaling to suppression of adenomatous polyposis coli, a Wnt/β-catenin inhibitor.…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al demonstrated that also the up-regulated microRNA-155 (miR-155), markedly increased in HCV-infected patients, activates the Wnt signaling pathway with nuclear accumulation of β-catenin and the accompanying increase in cyclin D1, c-Myc, and survivin. It was also determined that a direct and functional target of miR-155 involved APC [89]. However, it was not until in vitro studies were conducted that interactions between HCV proteins and the Wnt/β-catenin signaling pathway were clarified.…”
Section: Wnt/β-catenin Pathway In Hcv-associated Liver Carcinogenesismentioning
confidence: 99%
“…Furthermore, multiple mutations at the chromosomales, genetics and epigenetics levels have been implicated as pathogenetic mechanisms in the development of HCC [26,27] . MicroRNA has been shown to aid in the transcription of HCC oncogenes and (Wnt) signaling, and it plays important roles in the development of HCC through the activation of β catenin, the overexpression of Wnt receptors and the inactivation of Ecadherin [28] .…”
Section: Molecular Pathogenesismentioning
confidence: 99%